Baby-daily: a real-time mobile application for monitoring baby’s health / Mohamad Fahmi Mohamad Shuhari - Mohamad Shuhari, Mohamad Fahmi (Faculty of Computer and Mathematical Sciences, 2019)
Baby-Daily is a mobile application for monitoring baby’s health that can be used by parent, caregiver and doctor. This application is developed to keep the baby’s health condition based on the statistical report that been generated through the parent or caregiver interaction on the events. It is because to overcome the problem that occur towards new parents that not well prepared for their newborn baby. This application also providing the reminders features that will notify the parent about their baby’s incoming events and help parent to be more prepared in handling their baby. In this application there is a platform for doctor to write and share their knowledge through this application. It is because the information in internet inaccurate. This application also comes with many features such as chatting platform, video streaming, medical post, reminder and notifications for all users for delivering useful information specifically about baby. It can help the parent to take care of their baby properly without any problem and misleading information. Besides, Baby-Daily also help parent to keep notify their incoming appointment with hospitals also vaccination. Furthermore, based on the result of usability testing, it shows that 93.3% agreed that they satisfy with this overall application.